The Interaction of form and Content: Syntactic Constructions and Grammatical Environment - Trobevšek Drobnak, Frančiška (Studia Anglica Posnaniensia, 2010)
In diachronic linguistics, the Naturalness Theory purports to unravel the seemingly random distribution of linguistic variants at the early stage of their assertion, when no other tangible functional, contextual or pragmatic motivation exists. The paper presents the results of three empirical studies, which confirm that the complexity of grammatical environment is instrumental in the choice between elective morphosyntactic constructions. Special attention is paid to the relevance of traditional grammatical parameters in defining grammatical environment as complex.